Study of some features of the foreign countries special police units activities - М. О. Borovyk (Law and Safety)
The activity of special police units of such countries as Poland, Germany and the USA has been analyzed. The analysis has been carried out in order to determine the priority areas of the domestic special police units member’s personality formation, as well as in the extreme combat conditions.